Management of biocontaminated waste in health establishments administered by the Regional Governments of Peru - Esteban Jiménez, José Luis Ricardo (2022)
Health facilities generate thousands of tons of waste each year, including non-hazardous waste, hazardous substances, radioactive substances, and infectious substances. This number is increasing as our country continues to develop, as is public concern about its negative effects on human health. Through this study, an adequate management of hospital waste from its origin to its final disposal is suggested, focusing on the correct segregation of waste, since this will minimize the impact. In each medical facility it is necessary to establish a biological treatment system for contaminated waste; in accordance with the provisions of the Hygiene Technical Reference: "Management and total management of solid waste in health establishments, medical support services and research centers", through which the physical, chemical or biological properties of the biologically contaminated waste, to reduce or eliminate the potential danger to your health and the environment, until its final disposal. For this reason, we consider that in each seat of regional government a plan for the generation of biocontaminated waste from EESS should be implemented, managed by the Ministry of Health, with alternative treatment solutions to disinfect biocontaminated waste, the receptivity of the infrastructure for final treatment of biological polluting waste, in an ecological environment.